Valuing the Recreation Uses of Natural Resources: The Travel Cost Method - Elizabeth F. Pienaar (EDIS)
Many available statistics provide evidence that outdoor recreation in Florida generates economic value, but these data do not capture the full recreation value of Florida’s natural resources. The Travel Cost Method (TCM) approach may be applied in cost-benefit analysis and in natural resource damage assessments where recreation values are relevant. This 8-page fact sheet summarizes and synthesizes economic texts on TCM and provides an overview of a case study in which the TCM was used to estimate the nature-based recreation use value of the Apalachicola River Region in Florida. Written by Elizabeth F. Pienaar and published by the UF Department of Wildlife Ecology and Conservation, January 2014.